Oral Bisoprolol for the treatment of non-resolving central serous chorioretinopathy: A case report - Vingolo EM; Napolitano G; Rigoni E; De Rosa V (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2020)
Purpose: To evaluate the effect of the beta blocker Bisoprolol in the treatment of chronic central serous chorioretinopathy (CSC). Methods: Five patients with non-resolving CSC were treated with oral Bisoprolol 2,5 mg once a day for three months. The best-corrected visual acuity (BCVA), central macular thickness (CMT) and sub-retinal fluid (SRF) horizontal diameter recorded at baseline and at 1, 2, and 3 months by optical coherence tomography (OCT) were analyzed. Results: All the patients achieved a full visual recovery after 3 months of treatment and there was no evidence of SRF at the last OCT follow-up. No side effect was recorded. Conclusions: These results suggest that oral Bisoprolol may be effective in the treatment of chronic CSC and could be considered as a potential therapy choice in those cases at risk of diffuse retina pigment epitheliopathy.